Method for coating nano material on outer surface of micro-flow pipeline

By performing hydrophilic modification on the outer surface of the microfluidic pipeline and using hydrophobic coating molds, uniform coating of carbon nanotube films is achieved, solving the problems of low utilization of carbon nanotube solutions and uneven coating of substrates in the prior art, and improving the utilization rate and coating efficiency of nanomaterials.

CN119658901APending Publication Date: 2025-03-21XIAN JIAOTONG LIVERPOOL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411907927.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has problems in the preparation of carbon nanotube thin films that the carbon nanotube solution utilization rate is low and it is difficult to obtain a uniform surface coating film on non-planar substrates, especially tubular substrates.

Method used

By utilizing the selective adsorption characteristics of the nanomaterial, hydrophilic modification and hydrophobic coating molds are combined on the outer surface of the microfluidic pipeline to achieve autonomous selective adsorption and uniform coating of the nanomaterial.

Benefits of technology

The utilization rate of nanomaterials is improved, and the nanomaterial film is uniformly coated on non-planar substrates, with gentle process conditions and high preparation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119658901A_ABST
    Figure CN119658901A_ABST
Patent Text Reader

Abstract

The invention relates to a method for coating a nano material on the outer surface of a micro-flow pipeline. The method comprises the following steps: S1, preparing a nano material dispersion liquid; s2, performing hydrophilic modification on the outer surface of the micro-flow pipeline, namely irradiating the outer surface of the micro-flow pipeline by adopting ultraviolet light to perform hydrophilic modification, and enabling the contact angle after modification to be 60-80 degrees; s3, a hydrophobic coating mold is prepared, specifically, a hydrophobic high polymer material is arranged on the inner surface of the coating mold, and the hydrophobic coating mold with the inner surface contact angle being 90-120 degrees is obtained; and S4, coating: placing the microflow pipeline of which the outer surface is subjected to hydrophilic modification in the hydrophobic coating mold, then adding the nano material dispersion liquid into the hydrophobic coating mold, then drying the hydrophobic coating mold, and demolding to obtain the microflow pipeline of which the outer surface is coated with the nano material. The method for coating the nano material on the outer surface of the micro-flow pipeline has the characteristics that the utilization rate of the nano material dispersion liquid is high, the outer surface of the micro-flow pipeline is uniformly coated, the preparation efficiency is high, and the method can be suitable for micro-flow pipelines in any shape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano material coating, in particular to a method for coating nano material on the outer surface of a microfluidic pipeline. Background Art

[0002] Carbon nanotubes (CNTs) have become a very important and promising material among nanomaterials, due to their outstanding electrical, mechanical and thermal properties. The introduction of CNT films on flexible substrates has the potential to obtain low-cost, highly flexible electronic devices.

[0003] At present, the effective methods for preparing carbon nanotube films on flexible substrates include drop coating, dip coating, pulling method, spraying method, etc. Among them, the thickness of carbon nanotube films prepared by drop coating is difficult to control accurately, and the process is short, but the density of the film at the center and edge of the substrate is uneven, which is not conducive to the stability of device performance; the carbon nanotube film prepared by dip coating has good uniformity, but the process is time-consuming and requires a large amount of carbon nanotube solution. The density of the overall network film is low, which affects the performance of subsequent prepared devices; the carbon nanotube film prepared by pulling method has good uniformity and stability, but the process requires a large amount of basic liquid consumption and a large amount of cleaning solvent; the spraying method requires the use of spray gun equipment, and the spray gun has a large spraying area, uneven spraying, and is prone to waste of spray liquid.

[0004] In summary, the current methods for preparing carbon nanotube films all have the problem of low utilization rate of carbon nanotube solution, and it is difficult to obtain a uniform coating film on the surface when processing non-planar substrates, especially tubular substrates. Therefore, it is an urgent problem to design a method with high utilization rate of carbon nanotube solution and uniform coating of carbon nanotube film on the surface of non-planar substrates. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the present application provides a method for coating nanomaterials on the outer surface of a microfluidic channel by utilizing the selective adhesion characteristics of nanomaterials to hydrophilic and hydrophobic interfaces, which specifically includes the following steps:

[0006] S1, preparing a nanomaterial dispersion, wherein the nanomaterial is selected from carbon nanotubes, carbon fibers, graphene, and silver nanowires;

[0007] S2, hydrophilic modification of the outer surface of the microfluidic channel, using ultraviolet light to irradiate the outer surface of the microfluidic channel for hydrophilic modification, wherein the contact angle of the hydrophilic modified outer surface of the microfluidic channel is 60 to 80°;

[0008] S3, preparing a hydrophobic coating mold, setting a hydrophobic polymer material on the inner surface of the coating mold to perform surface hydrophobic modification, and obtaining a hydrophobic coating mold with an inner surface contact angle of 90 to 120°;

[0009] S4, coating, placing the microfluidic channel with hydrophilic modified outer surface in the hydrophobic coating mold, then adding the nano material dispersion into the hydrophobic coating mold, and then drying to obtain the microfluidic channel with nano material coated outer surface.

[0010] More specifically, the material of the microfluidic channel is selected from any one of PDMS, PBAT, PVA, polyimide, and thermoplastic elastomer.

[0011] More specifically, the microfluidic channel is linear or non-linear with at least one bending curvature.

[0012] More specifically, the bending curvature is 0.06 to 0.33.

[0013] More specifically, the step S1 is specifically: preparing a nanomaterial dispersion liquid, adding carbon nanotubes to the dispersion liquid, and using ultrasound to evenly disperse the carbon nanotubes in the dispersion liquid to obtain the nanomaterial dispersion liquid. More specifically, during the ultrasound process, the power of the ultrasound device is 100 to 400 W, and the ultrasound time is 10 to 30 minutes.

[0014] More specifically, the dispersion liquid is selected from any one of water, ethanol, isopropanol and DMF.

[0015] More specifically, the concentration of carbon nanotubes in the nanomaterial dispersion is 5 to 50 μg / mL.

[0016] In a further specific step S2, during the process of ultraviolet light irradiating the outer surface of the microfluidic channel, the power of the ultraviolet light irradiation device is 50 to 100 W, and the ultraviolet light irradiation time is 10 to 30 minutes.

[0017] In a further specific step S3, the hydrophobic polymer material is selected from any one of PTFE and fluorocarbon resin.

[0018] More specifically, in step T4, during the drying process, the drying temperature is 50-80° C., and the drying time is 2-4 hours.

[0019] More specifically, the nanomaterial is used to coat a portion of the outer surface of the microfluidic channel, and the portion of the outer surface is a non-circular closed outer surface area.

[0020] The beneficial effects of this application are:

[0021] The present application utilizes the difference in contact angle between the hydrophobic mold and the hydrophilic microfluidic channel surface to make the nanomaterials autonomously and selectively adsorbed on the outer surface of the microfluidic channel, and after drying and demoulding, a nanomaterial film with uniform texture can be obtained. The method designed in the present application has high utilization rate of nanomaterials, mild process conditions, and high preparation efficiency. By utilizing the pattern of the inner mold groove of the hydrophobic mold, various patterns of nanomaterial films can be conveniently and quickly coated on non-planar substrates. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the process flow in this application;

[0023] Figure 2 is a schematic diagram of coating a carbon nanotube film on the outer surface of a microfluidic channel in the present application;

[0024] Figure 3 is an electron microscope image of a carbon nanotube film on the outer surface of a microfluidic channel in the present application;

[0025] Figure 4 is the performance test result of Example 1 in this application;

[0026] Figure 5 is the performance test result of Example 2 in this application;

[0027] Figure 6 This is the performance test result of Example 3 in this application. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the specific implementation methods of the present invention are clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The present invention provides a method for coating nanomaterials on the outer surface of a microfluidic channel. The method can coat the nanomaterials on the outer surface or part of the outer surface of the microfluidic channel according to actual needs. Figure 2The three coating areas shown in a, b, and c can also be coated with a layer of nanomaterial film on the outer surface of a microfluidic channel of any shape, a linear nanomaterial film can be coated on the outer surface, or a nanomaterial film with other patterns can be coated on the outer surface. This method can be applicable to linear microfluidic channels, and can also be applicable to non-linear microfluidic channels with at least one bending curvature, and the bending curvature can be between 0.06 and 0.33. The material of the microfluidic channel can be PDMS precursor solution, Ecoflex (PBAT), polyimide acid, thermoplastic elastomer, PVA or other high molecular polymer materials. The method designed by the present invention for coating nanomaterials on the outer surface of a microfluidic channel can be applied to biosensors such as flow measurement fields, and can be specifically applied to the coating of nanofunctional materials on the outer surface of a velocity measuring channel in a flow sensor, and the nanomaterials are evenly and stably attached after coating.

[0030] The process of coating nanomaterials on the outer surface of microfluidic channels is as follows Figure 1 As shown, specifically including:

[0031] S1. Prepare nanomaterial dispersion. The nanomaterial can be carbon nanotubes, graphene, carbon fiber or a mixture thereof, or silver nanowires. The selected nanomaterial needs to ensure that the nanomaterial has good selective adsorption when the contact angles of the two interfaces differ greatly. Taking carbon nanotube materials as an example, when preparing nanomaterial dispersion: first, add carbon nanotubes to the dispersion, the dispersion solvent can be water, or any one of the organic solvents ethanol, isopropanol, and DMF. After adding, stir well and then use ultrasound to evenly disperse the carbon nanotubes in the dispersion to obtain a nanomaterial dispersion. Preferably, during the ultrasonic process, the power of the ultrasonic device is 100 to 400 W, the ultrasonic time is 10 to 30 min, and a cell crusher can also be used during the ultrasonic mixing process. In order to ensure that the conductive properties of the nanomaterial itself in the nanomaterial dispersion are not destroyed, the ultrasonic time and ultrasonic power should not be too large, and excessive ultrasonic energy should be avoided to break nanomaterials such as carbon nanotubes, carbon fibers, and silver nanowires.

[0032] The microfluidic channel coated by the coating method designed in the present application can be used for biosensors. To ensure good biocompatibility and long-term stability, in some specific embodiments, when used as a coating for a biosensor, carbon nanotubes are preferably used as the nanomaterial, and water is preferably used as the dispersion liquid. To ensure that the nanomaterial dispersion liquid can be evenly attached to the outer surface of the microfluidic channel and has good electrical conductivity and mechanical tensile properties, the concentration of the nanomaterial dispersion liquid is preferably 0.1 to 50 μg / mL.

[0033] S2. Hydrophilic modification of the outer surface of the microfluidic channel. The outer surface of the microfluidic channel is hydrophilic modified by irradiating the microfluidic channel with ultraviolet light. The power of the ultraviolet light irradiation device is 50 to 100 W, and the ultraviolet light irradiation time is 10 to 30 minutes. After the hydrophilic modification, the contact angle of the outer surface of the microfluidic channel is 60 to 80°.

[0034] S3, preparing a hydrophobic coating mold. A hydrophobic polymer material is arranged on the inner surface of the coating mold to obtain a hydrophobic coating mold, and the hydrophobic polymer material is selected from any one of PDMS, PBAT, PVA, polyimide, and thermoplastic elastomer. The contact angle of the inner surface of the hydrophobic coating mold is 90 to 120 degrees.

[0035] When the nanomaterial is partially coated on the outer surface of the microfluidic channel, the pattern of the coating mold groove is preset according to the coating pattern to be coated. For example, when a linear coating is to be coated on the outer surface of the microfluidic channel, the pattern of the coating mold groove is also linear; when a patterned coating is to be coated on the outer surface of the microfluidic channel (it can be a pattern adapted to the contact of the wire lead), the pattern of the coating mold groove should also be adapted to the pattern. The material of the mold is preferably selected to be firmly attached to the hydrophobic polymer material and not react with the nanomaterial.

[0036] S4. Place a microfluidic channel with an outer surface contact angle of 60 to 80° in a hydrophobic coating mold with an inner surface contact angle of 90 to 120°, and then add a nanomaterial dispersion into the hydrophobic coating mold. Since the nanomaterial has selective attachment to the hydrophilic-hydrophobic interface, the nanomaterial will be adsorbed on the outer surface of the microfluidic channel in the shape of a groove, and then dried at a temperature of 50 to 80°C for 2 to 4 hours to obtain a microfluidic channel with a nanomaterial coated on the outer surface. The thickness of the nanomaterial coating is relatively thin, and can reach a thickness close to that of a monomolecular layer.

[0037] It is worth noting that in the method for coating nanomaterials on the outer surface of a microfluidic channel designed in the present invention, steps S1, S2, and S3 are not strictly in the order of S1→S2→S3. S1, S2, and S3 can be interchanged, and it is only necessary to complete the first three steps before step S4.

[0038] Based on the above preparation method, some specific embodiments and comparative examples are listed below. In the embodiments and comparative examples, the nanomaterials are all carbon nanotubes, the carbon nanotubes are all dispersed in deionized water, the ultrasonic equipment is 880W, 30% power ultrasonic time is used for 15 minutes, and the microfluidic pipeline material is all PDMS.

[0039] Example 1

[0040] S1. Prepare a carbon nanotube dispersion according to the above method, with a concentration of 5 ug / mL.

[0041] S2. Ultraviolet light was used to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel was 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power was 80 W and the irradiation time was 20 mins. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel was measured to be 70°.

[0042] S3, sticking PTFE hydrophobic polymer material on the inner surface of the coating mold, the thickness of the hydrophobic polymer material is 30 μm, and the contact angle of the inner surface of the hydrophobic coating mold is 110°;

[0043] S4, placing the microfluidic channel with an outer surface contact angle of 70° in a hydrophobic coating mold with an inner surface contact angle of 110°, then adding the carbon nanotube dispersion into the hydrophobic coating mold, and drying at 60°C for 120 minutes to obtain a microfluidic channel with an outer surface coated with carbon nanotube material. The electron microscope image of the surface nanomaterial coating is as follows Figure 3 As shown, the resistance is measured as the pipe stretch rate changes, and the results are as follows Figure 4 shown.

[0044] Example 2

[0045] S1. Prepare a carbon nanotube dispersion according to the above method, with a concentration of 10ug / ml.

[0046] S2. Use ultraviolet light to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel is 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power is 80 w and the irradiation time is 20 min. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel is measured to be 70°.

[0047] S3, sticking PTFE hydrophobic polymer material on the inner surface of the coating mold, the thickness of the hydrophobic polymer material is 30 μm, and the contact angle of the inner surface of the hydrophobic coating mold is 110°;

[0048] S4, placing the microfluidic channel with an outer surface contact angle of 70° in a hydrophobic coating mold with an inner surface contact angle of 110°, then adding the carbon nanotube dispersion into the hydrophobic coating mold, and drying at 60°C for 120 minutes to obtain a microfluidic channel with an outer surface coated with carbon nanotube material. The electron microscope image of the surface nanomaterial coating is as follows Figure 3 As shown, the resistance is measured as the pipe stretch rate changes, and the results are as follows Figure 5 shown.

[0049] Example 3

[0050] S1. Prepare a carbon nanotube dispersion according to the above method, with a concentration of 50ug / ml.

[0051] S2. Use ultraviolet light to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel is 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power is 80 w and the irradiation time is 20 min. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel is measured to be 70°.

[0052] S3, sticking PTFE hydrophobic polymer material on the inner surface of the coating mold, the thickness of the hydrophobic polymer material is 30 μm, and the contact angle of the inner surface of the hydrophobic coating mold is 110°;

[0053] S4, placing the microfluidic channel with an outer surface contact angle of 70° in a hydrophobic coating mold with an inner surface contact angle of 110°, then adding the carbon nanotube dispersion into the hydrophobic coating mold, and drying at 60°C for 120 minutes to obtain a microfluidic channel with an outer surface coated with carbon nanotube material. The electron microscope image of the surface nanomaterial coating is as follows Figure 3 As shown, the resistance is measured as the pipe stretch rate changes, and the results are as follows Figure 6 shown.

[0054] Example 4

[0055] S1. Prepare a carbon nanotube dispersion according to the above method, with a concentration of 5ug / ml.

[0056] S2. Use ultraviolet light to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel is 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power is 80 w and the irradiation time is 30 min. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel is measured to be 60°.

[0057] S3, sticking PTFE hydrophobic polymer material on the inner surface of the coating mold, the thickness of the hydrophobic polymer material is 30 μm, and the contact angle of the inner surface of the hydrophobic coating mold is 110°;

[0058] S4. Place the microfluidic channel with an outer surface contact angle of 60° in a hydrophobic coating mold with an inner surface contact angle of 110°, then add the carbon nanotube dispersion into the hydrophobic coating mold, and dry at 60°C for 120 minutes to obtain a microfluidic channel with an outer surface coated with carbon nanotube material.

[0059] Example 5

[0060] S1. Prepare a carbon nanotube dispersion according to the above method, with a concentration of 5ug / ml.

[0061] S2. Use ultraviolet light to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel is 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power is 80 w and the irradiation time is 20 min. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel is measured to be 70°.

[0062] S3, sticking PTFE hydrophobic polymer material on the inner surface of the coating mold, the thickness of the hydrophobic polymer material is 30 μm, and the contact angle of the inner surface of the hydrophobic coating mold is 110°;

[0063] S4. Place the microfluidic channel with an outer surface contact angle of 70° in a hydrophobic coating mold with an inner surface contact angle of 110°, then add the carbon nanotube dispersion into the hydrophobic coating mold, and dry at 80°C for 100 minutes to obtain a microfluidic channel with an outer surface coated with carbon nanotube material.

[0064] Example 6

[0065] S1. Prepare silver nanowire dispersion according to the above method, with a concentration of 5ug / ml.

[0066] S2. Ultraviolet light was used to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel was 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power was 80 W and the irradiation time was 20 mins. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel was measured to be 70°.

[0067] S3, sticking PTFE hydrophobic polymer material on the inner surface of the coating mold, the thickness of the hydrophobic polymer material is 30 μm, and the contact angle of the inner surface of the hydrophobic coating mold is 110°;

[0068] S4. Place a microfluidic channel with an outer surface contact angle of 70° in a hydrophobic coating mold with an inner surface contact angle of 110°, then add a silver nanowire dispersion into the hydrophobic coating mold, and dry at 60°C for 120 minutes to obtain a microfluidic channel with hard nanowires coated on the outer surface. The change in resistance with the stretching rate of the channel was measured, and it was found that the resistance of the surface silver nanowire coating changed little with the stretching rate of the channel, and the biological perception ability of the silver nanowire material coating was weak.

[0069] Comparative Example 1

[0070] S1. Prepare a carbon nanotube dispersion according to the above method, with a concentration of 0.1 ug / ml.

[0071] S2. Use ultraviolet light to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel is 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power is 80 W and the irradiation time is 20 min. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel is measured to be 70°.

[0072] S3, sticking PTFE hydrophobic polymer material on the inner surface of the coating mold, the thickness of the hydrophobic polymer material is 30 μm, and the contact angle of the inner surface of the hydrophobic coating mold is 70°;

[0073] S4. Place the microfluidic channel with an outer surface contact angle of 70° in a hydrophobic coating mold with an inner surface contact angle of 110°, then add the carbon nanotube dispersion into the hydrophobic coating mold, and dry at 60° C. for 120 min.

[0074] Since the concentration of carbon nanotubes is too low, very little nanomaterial is selectively attached to the outer surface of the microfluidic channel, and the nanomaterial coating on the outer surface of the microfluidic channel is incomplete.

[0075] Comparative Example 2

[0076] S1. Prepare a carbon nanotube dispersion according to the above method, with a concentration of 5ug / ml.

[0077] S2. Use ultraviolet light to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel is 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power is and the irradiation time is 5 min. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel is measured to be 90°.

[0078] S3, sticking PTFE hydrophobic polymer material on the inner surface of the coating mold, the thickness of the hydrophobic polymer material is 30 μm, and the contact angle of the inner surface of the hydrophobic coating mold is 110°;

[0079] S4. Place the microfluidic channel with an outer surface contact angle of 90° in a hydrophobic coating mold with an inner surface contact angle of 110°, then add the carbon nanotube dispersion into the hydrophobic coating mold, and dry at 60° C. for 120 min.

[0080] Since the contact angle of the outer surface of the microfluidic channel is too small to differ from the contact angle of the inner surface of the mold, the nanomaterial selectively adheres to very little of the outer surface of the microfluidic channel, and the nanomaterial coated on the outer surface of the microfluidic channel is incomplete.

[0081] Comparative Example 3

[0082] S1. Prepare a carbon nanotube dispersion according to the above method, with a concentration of 5ug / ml.

[0083] S2. Ultraviolet light was used to irradiate the outer surface of a linear microfluidic channel. The microfluidic channel was 5 cm long, with an inner diameter of 500 um and an outer diameter of 800 um. The ultraviolet irradiation power was 80 um and the irradiation time was 20 min. After irradiation treatment, the contact angle of the hydrophilic modified outer surface of the microfluidic channel was measured to be 70°.

[0084] S3. No sticky hydrophobic polymer material is provided on the inner surface of the coating mold, and the contact angle of the inner surface of the coating mold is 90°;

[0085] S4. Place the microfluidic channel with an outer surface contact angle of 70° in a hydrophobic coating mold with an inner surface contact angle of 90°, then add the carbon nanotube dispersion into the hydrophobic coating mold, and dry at 60° C. for 120 min.

[0086] Since the contact angle of the outer surface of the microfluidic channel is too small to differ from the contact angle of the inner surface of the mold, the nanomaterial selectively adheres to very little of the outer surface of the microfluidic channel, and the nanomaterial coated on the outer surface of the microfluidic channel is incomplete.

[0087] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for coating the outer surface of a microfluidic channel with nanomaterials, characterized in that: The following steps are involved: S1, preparing a nanomaterial dispersion, wherein the nanomaterial is selected from carbon nanotubes, carbon fibers, graphene, and silver nanowires; S2, hydrophilic modification of the outer surface of the microfluidic channel, using ultraviolet light to irradiate the outer surface of the microfluidic channel for hydrophilic modification, wherein the contact angle of the hydrophilic modified outer surface of the microfluidic channel is 60 to 80°; S3, preparing a hydrophobic coating mold, setting a hydrophobic polymer material on the inner surface of the coating mold to perform surface hydrophobic modification, and obtaining a hydrophobic coating mold with an inner surface contact angle of 90 to 120°; S4, coating, placing the microfluidic channel with hydrophilic modified outer surface in the hydrophobic coating mold, then adding the nano material dispersion into the hydrophobic coating mold, and then drying to obtain the microfluidic channel with nano material coated outer surface.

2. The method for coating nanomaterials according to claim 1, characterized in that: The microfluidic channel material is selected from any one of PDMS, PBAT, PVA, polyimide, and thermoplastic elastomer.

3. The method for coating nanomaterials according to claim 1, characterized in that: The microfluidic channel is linear or non-linear with at least one bending curvature.

4. The method for coating nanomaterials according to claim 3, characterized in that: The bending curvature is 0.06 to 0.

33.

5. The method for coating nanomaterials according to claim 1, characterized in that: The step S1 specifically comprises: preparing a nano material dispersion liquid, adding carbon nanotubes into the dispersion liquid, and using ultrasound to evenly disperse the carbon nanotubes in the dispersion liquid to obtain the nano material dispersion liquid.

6. The method for coating nanomaterials according to claim 5, characterized in that: The dispersion liquid is selected from any one of water, ethanol, isopropanol and DMF.

7. The method for coating nanomaterials according to claim 5, characterized in that: The concentration of carbon nanotubes in the nano material dispersion is 5 to 50 μg / mL.

8. The method for coating nanomaterials according to claim 1, characterized in that: In step S2, during the process of ultraviolet light irradiating the outer surface of the microfluidic channel, the power of the ultraviolet light irradiation device is 50 to 100 W, and the ultraviolet light irradiation time is 10 to 30 minutes.

9. The method for coating nanomaterials according to claim 1, characterized in that: In step S3, the hydrophobic polymer material is selected from any one of PTFE and fluorocarbon resin.

10. The method for coating nanomaterials according to any one of claims 1 to 9, characterized in that: It is used for coating nanometer materials on the partial outer surface of a microfluidic channel, wherein the partial outer surface is a non-circular closed outer surface area.